Cardiovascular risk factors and clinical outcomes among patients hospitalized with COVID-19: findings from the World Heart Federation COVID-19 study - Prabhakaran, Dorairaj (2022)
© 2022 The Author(s). This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International License (CC-BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. See http://creativecommons.org/ licenses/by/4.0/.